1998
DOI: 10.1002/(sici)1097-4628(19981219)70:12<2439::aid-app16>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Silkworm silk as an engineering material

Abstract: While silk exhibits high values of tensile strength and stiffness, these properties are compromised by their poor reproducibility. We present the results of experiments aimed at characterizing the variability of tensile properties exhibited by cocoon silk from Bombyx mori silkworms. Scanning electron microscopy is used to measure an average diameter for individual test specimens; the interspecimen variability of diameter is quantified and found to be inadequately represented by standard deviation. When load-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
192
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 246 publications
(213 citation statements)
references
References 9 publications
14
192
2
Order By: Relevance
“…Obviously, on the time scale of the experiment, a single relaxation time of 10 s describes the data well. The equilibrium and the relaxing moduli are G e 5:1 GPa, G 6:6 GPa, yielding G g 11:7 GPa, in good agreement with [23].…”
supporting
confidence: 81%
“…Obviously, on the time scale of the experiment, a single relaxation time of 10 s describes the data well. The equilibrium and the relaxing moduli are G e 5:1 GPa, G 6:6 GPa, yielding G g 11:7 GPa, in good agreement with [23].…”
supporting
confidence: 81%
“…Samples were retrieved and glued on perforated cardboard frames (Pérez-Rigueiro et al, 1998) . The load applied to the sample was measured with a balance (AND 1200 G, A&D Instruments, Oxford, UK, resolution ±10·mg) attached to the lower end of the sample.…”
Section: Methodssupporting
confidence: 65%
“…10 shows the stress-strain curves of regenerated silkworm fibers spun according the IPSD procedure. The range of stress-strain curves of natural silkworm silk fibers (Pérez-Rigueiro et al, 1998) is also indicated. The elastic modulus of the as-spun fibers lies within the range observed in natural fibers.…”
Section: 1mentioning
confidence: 99%